2017
DOI: 10.3390/ijms18040754
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Cas9 Mediated Gene-Silencing of the Mutant Huntingtin Gene in an In Vitro Model of Huntington’s Disease

Abstract: Huntington’s disease (HD) is a fatal neurodegenerative genetic disease characterized by a loss of neurons in the striatum. It is caused by a mutation in the Huntingtin gene (HTT) that codes for the protein huntingtin (HTT). The mutant Huntingtin gene (mHTT) contains extra poly-glutamine (CAG) repeats from which the translated mutant huntingtin proteins (mHTT) undergo inappropriate post-translational modifications, conferring a toxic gain of function, in addition to its non-functional property. In order to curb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 45 publications
0
47
0
6
Order By: Relevance
“…Subsequent analyses revealed a large 44-kb deletion leading to the complete inactivation of mHTT without affecting the normal allele. According to the aforementioned studies and several others [67][68][69], CRISPR/Cas9 has the ability to solely inhibit mHTT expression in a specific brain region and thus has rapidly become the most promising gene-editing tool for neurodegenerative diseases such as HD. However, a question remains regarding the safety of the CRISPR/Cas9 system, which is now being tested in animal models to establish an effective and completely safe procedure before its application in humans [70].…”
Section: Gene Therapy For Hdmentioning
confidence: 99%
“…Subsequent analyses revealed a large 44-kb deletion leading to the complete inactivation of mHTT without affecting the normal allele. According to the aforementioned studies and several others [67][68][69], CRISPR/Cas9 has the ability to solely inhibit mHTT expression in a specific brain region and thus has rapidly become the most promising gene-editing tool for neurodegenerative diseases such as HD. However, a question remains regarding the safety of the CRISPR/Cas9 system, which is now being tested in animal models to establish an effective and completely safe procedure before its application in humans [70].…”
Section: Gene Therapy For Hdmentioning
confidence: 99%
“…The deletion mutations created following CRISPR‐Cas9‐based editing showed reduced CAG repeat expansions in the HD cells. Further analysis showed that mHTT was reduced compared with controls …”
Section: Hd Gene Editing Using Crispr‐cas9mentioning
confidence: 99%
“…Badania przedkliniczne sugerują zwiększoną efektywność wprowadzenia zmian w DNA, w skutek jego przecięcia przez system CRISPR-Cas9, poprzez mechanizm niehomologicznego łączenia końców (NHEJ, ang. non-homologous end joining) [53]. Przy pomocy tej technologii można wpłynąć na transkrypcję HTT na wiele sposobów począwszy od wycięcia powtórzeń CAG czy poprzez przesunięcie ramki odczytu i wystąpienie w ten sposób przedwczesnych kodonów stop [33,54,55].…”
Section: Technologia Crispr-cas9unclassified